2018
DOI: 10.1007/s11356-018-2508-y
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response

Abstract: Phytoremediation is a cost-effective and eco-friendly technique for the removal of heavy metal-contaminated soils and water. The less availability and mobility of heavy metals in medium decreased the efficiency of this technique. The mobility and availability of these metals in the medium can be enhanced by the addition of organic chelators. The present study was conducted to investigate the possibility of glutamic acid (GA) in improving silver (Ag) phytoextraction by sunflower (Helianthus annuus L.). Differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
19
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 61 publications
10
19
1
Order By: Relevance
“…The increased Cr concentrations led to a significant decrease in the growth of the sunflower plants ( Table 1). Several studies regarding Cr-induced toxic effects on sunflower plant have been widely reported (Farid et al, 2017a;Farid et al, 2018a;Farid et al, 2018b). Chromium-induced toxicity was shown to severely impair nutrient uptake in plants, leading to reduced biomass production and stunted growth (Tauqeer et al, 2016;Fozia et al, 2008).…”
Section: Agronomic Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased Cr concentrations led to a significant decrease in the growth of the sunflower plants ( Table 1). Several studies regarding Cr-induced toxic effects on sunflower plant have been widely reported (Farid et al, 2017a;Farid et al, 2018a;Farid et al, 2018b). Chromium-induced toxicity was shown to severely impair nutrient uptake in plants, leading to reduced biomass production and stunted growth (Tauqeer et al, 2016;Fozia et al, 2008).…”
Section: Agronomic Traitsmentioning
confidence: 99%
“…Heavy metals can also enter the food chain and accumulate in plant and human body tissues (Rizwan et al, 2016). Chromium is a relatively abundant heavy metal in the topsoil owing to its utility in various industrial processes (Farid et al, 2018a). It is used both in the electroplating industry as an anticorrosive and antibiofouling agent, as well as in steel and automobile manufacturing (Farid et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar toxic effects of Pb were reported in Brassica napus [ 24 ] and A. bettzickiana [ 15 ]. Similar to other organic acids, the AA growth-promoting effect is confirmed in the literature where organic acids such as citric acid (2.5, 5, and 10 mM), glutamic acid (2.5 and 5 mM), and ascorbic acid (5 mM) were used for Brassica napus, sunflower [ 24 , 25 ], Lemna minor L. [ 26 ], and Solanum nigrum L. [ 27 ], respectively, in the presence of HMs stress.…”
Section: Discussionmentioning
confidence: 67%
“…Among these organic compounds, flavonoids, lipids, sugars, amino acids, and LMWOAs such as acetic, citric, oxalic, propionic, butyric, malic, fumaric, malonic, and succinic acids have been widely found in the plant's rhizosphere [68][69][70]. These organic compounds react with metals to form complexes, which are adsorbed by the roots and then translocated into the aboveground parts of plants, and have been recently used as environmental friendly remediation of contaminated soils [71,72]. For a better understanding of our results, chemical extraction was firstly performed on unamended and amended soils with a mixture of organic acids and then, the metal phytoavailability was studied using three indicators.…”
Section: Concentrations Of Transition Alkali and Alkaline Earth Metmentioning
confidence: 99%